(untitled) (Journal of Medical & Health Sciences Review, 2025)
Background: BPH, also known as benign prostatic hypertrophy, is a pathological disorder characterized by the uncontrolled growth of the prostate’s cellular components. Sonographic Evaluation of Prostate Size and its Correlation with Age and post micturition residual volume (PMRV) in Patients with Benign Prostatic Hyperplasia Benign prostatic hyperplasia is a common health problem affecting men older than 50 years. Objective: To determine the frequency of prostatic urethral changes in benign prostate hyperplasia patients and to evaluate the association between benign prostate hyperplasia with age. Methodology: This study was approved by the Clinical Research Ethics Committee of Institute of Paramedical Sciences, Khyber Medical University, and Peshawar. Cross sectional descriptive study conducted at DHQ Hospital Batkhela district Malakand KPK using non-probability convenient Sampling techniques. The study included all the patients referred to ultrasound scan with lower urinary tract symptoms (LUTS). After informed consent data was collected through pre- structured questionnaire proforma and analyzed on SPSS version 20. Results: Sample size calculated is 188 using 95% confidence level and 5% level of significance. There is significant Correlation between prostate sizes with age that is Prostate size tends to increase with age. The most common age group was 60–69 years, accounting for 28% of the cases and most frequently observed prostate gland size ranged between 30 g to 39 g, seen in 42.0% of the cases. Conclusion: prostate size increase with increase in age and their no correlation between post void residual volume and prostate size.